Changes in the levels of marker molecules salivary α-amylase and cortisol as a stress response to everyday activities of general practitioners in rural areas of the Republic of Bulgaria - Adolf Alakidi; Iliyan Dimitrov; Anelia Bivolarska; Vanina Mihaylova (James Cook University, 2023)
Introduction: Stress is a phenomenon accompanying everyday life. Various reactions of the body are activated during stress, including activation of the hypothalamo-pituitary-adrenal endocrine axis and the autonomous nervous system. Their activity could be assessed by the measurement of biological stress marker molecules - salivary α-amylase and cortisol - on one side and heart rate, and blood pressure monitoring, on the other. The aim of the present study is to determine whether the daily professional routines cause stress development among general practitioners (GPs) who work in rural, distant areas in the territory of the Republic of Bulgaria. Methods: One hundred and twenty-eight GPs were asked to answer a questionnaire to assess their health conditions, habits, priority objectives and interests, as well as their moral and ethical relationships with the patients. On this basis 40 participants were selected and outlined for the present survey (n=40, mean age 55.92±8.8). Four salivary samples were collected from each participant during 1 week: two on Monday (one in the morning and one after work) and two on Friday, by the same mechanism. The salivary samples collection was followed by measurement of blood pressure and pulse. This non-invasive survey was based on an ELISA method for quantitative determination of the marker molecules in saliva. The blood pressure and pulse were measured by blood pressure monitor. Results: The levels of the salivary α-amylase were significantly higher at the end of the working day, especially on Friday (142.28±23.34 U/mL, p=0.018), but not between the beginning and the end of the week. The normal cortisol awakening response, characterized by a peak in the levels of cortisol after wake-up, followed by a slow decrease during the day, was detected only at the beginning of the week. The data show a significant impairment of this regularity at the end of the week. Moreover, the levels of cortisol, measured for the morning samples, show a decrease at the end of the week (25.73±10.51 ng/mL) in comparison to the beginning of the week (30.1±10.84, p=0.033). The analyses on the effect of smoking (p=0.002) and alcohol consumption (p=0.036) on stress development show a significant increase in the levels of the salivary α-amylase, but not on the levels of salivary cortisol. The changes in the blood pressure indicate stress development at the end of the week (p=0.04), while the pulse showed changes within a day rather than during the week. The values of the pulse were higher at the end of the day. Conclusion: The professional lives of the GPs who work in distant and rural places are associated with stress development. Different habits from the daily routine, such as alcohol consumption, smoking and physical activity, could be considered as modulators of stress development.